2011
DOI: 10.1155/2011/934269
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dispersal of the Crown-of-Thorns Sea Star,Acanthaster planci, across the Hawaiian Archipelago and Johnston Atoll

Abstract: The population structure of marine species is variable along the Hawaiian Archipelago; thus, it is important to understand dispersal and recruitment patterns for economically and ecologically important taxa to inform Ecosystem-based Management. Connectivity of the coral-eating crown-of-thorns sea star, Acanthaster planci, was examined from Johnston Atoll and 12 locations across the Hawaiian Archipelago. Sequences of mitochondrial DNA from 383 individuals were analyzed to infer patterns of gene flow among the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…[49,50], which must be maintained by limited larval and genetic exchange at these ocean scales. Within regions however, there is often very limited genetic structure [47,[51][52][53], indicative of extensive genetic exchange via widespread dispersal of larvae. Timmers et al [51] investigated genetic connectivity among CoTS populations in the northern Pacific, and revealed extensive gene flow along the 2500 km length of the Hawaiian archipelago, as well as between Hawai'i and Johnston Atoll separated by 865km.…”
Section: Minimum and Maximum Competency Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49,50], which must be maintained by limited larval and genetic exchange at these ocean scales. Within regions however, there is often very limited genetic structure [47,[51][52][53], indicative of extensive genetic exchange via widespread dispersal of larvae. Timmers et al [51] investigated genetic connectivity among CoTS populations in the northern Pacific, and revealed extensive gene flow along the 2500 km length of the Hawaiian archipelago, as well as between Hawai'i and Johnston Atoll separated by 865km.…”
Section: Minimum and Maximum Competency Periodsmentioning
confidence: 99%
“…Within regions however, there is often very limited genetic structure [47,[51][52][53], indicative of extensive genetic exchange via widespread dispersal of larvae. Timmers et al [51] investigated genetic connectivity among CoTS populations in the northern Pacific, and revealed extensive gene flow along the 2500 km length of the Hawaiian archipelago, as well as between Hawai'i and Johnston Atoll separated by 865km. Similarly, Harrison et al [53] found no genetic structure (using 27 optimized microsatellite loci) for outbreak populations of CoTS along the length of Australia's GBR.…”
Section: Minimum and Maximum Competency Periodsmentioning
confidence: 99%
“…For the most part, CoTS larvae are expected to be dispersed only 10s-100s km between reefs (Dight et al 1990a), if not entrained within the confines of their natal reef (Black and Moran 1991;Black 1993). Genetic sampling of CoTS populations demonstrated that there is effective connectivity (reflective of ecological significant levels of larval dispersal) between reefs separated by <1,000km (Timmers et al 2011;Yasuda et al 2015;Harrison et al 2017). However, there tends to be very strong genetic differentiation of CoTS populations among ocean basins and geographic provinces (Yasuda et al 2009;Timmers et al 2012), suggesting that there is extremely limited connectivity (and therefore, negligible larval dispersal) at distances of >1,000km.…”
Section: Question 6 and 7 (Larvae And Juveniles) -How Long Domentioning
confidence: 99%
“…Therefore, the primary factors that influence dispersal are i) how long larvae can persist while still retaining the capacity to settle (see section 2.5) and ii) oceanographic conditions (specifically, the strength and direction of water movement) during spawning and larval development (Timmers et al 2011). On the GBR, the extent to which larvae are retained and settle on their natal reefs (selfrecruitment) rather than being dispersed has been modelled for at least one small sub-region and may vary among years with changes in ENSO driven ocean current velocities (Wooldridge and Brodie 2015).…”
Section: Question 8 and 14 (Larvae And Juveniles) -What Factors Are Impmentioning
confidence: 99%
“…1C and D, respectively) from the samples, which were preserved in ethanol (>70%). We extracted DNA using the DNeasy blood & tissue kit (Qiagen), and directly sequenced partial mitochondrial DNA fragments amplified by using a previously published COI primer pair (Vogler et al 2008) and a putative control region primer pair (Timmers et al 2011). The latter primer pair can discriminate A. planci from some common sea stars such as Protoreaster nodosus, Linckia laevigata, and Culcita novaeguineae.…”
mentioning
confidence: 99%